2017
DOI: 10.1103/physreve.95.053002
|View full text |Cite
|
Sign up to set email alerts
|

Forces and torques on rigid inclusions in an elastic environment: Resulting matrix-mediated interactions, displacements, and rotations

Abstract: Embedding rigid inclusions into elastic matrix materials is a procedure of high practical relevance, for instance, for the fabrication of elastic composite materials. We theoretically analyze the following situation. Rigid spherical inclusions are enclosed by a homogeneous elastic medium under stick boundary conditions. Forces and torques are directly imposed from outside onto the inclusions or are externally induced between them. The inclusions respond to these forces and torques by translations and rotations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 82 publications
1
35
0
Order By: Relevance
“…They are distinct from active, stochastic forces generated by overlapping microtubule baskets being pushed apart by motor proteins. To model the passive forces, we describe the nuclei as inclusions within an elastic matrix motivated by models for cell arrangements (24)(25)(26)(27). The active force is described as an internuclear force with a constant activity time but a stochastic on-rate of a determined frequency to model the microtubule motor processivity and hopping rate.…”
Section: Introductionmentioning
confidence: 99%
“…They are distinct from active, stochastic forces generated by overlapping microtubule baskets being pushed apart by motor proteins. To model the passive forces, we describe the nuclei as inclusions within an elastic matrix motivated by models for cell arrangements (24)(25)(26)(27). The active force is described as an internuclear force with a constant activity time but a stochastic on-rate of a determined frequency to model the microtubule motor processivity and hopping rate.…”
Section: Introductionmentioning
confidence: 99%
“…Using linear elasticity theory, Puljiz et.al. obtained an analytic expression considering in first approximation mutual 2and 3-body elastic interactions among spherical particles [30,88]. In our present work, we assume an isotropic and incompressible elastic medium.…”
Section: Explicit Particle Structures-balance Of Local Forcesmentioning
confidence: 99%
“…Accordingly, we set ν = 0.5 and 3µ = E, where ν denotes the Poisson ratio, µ the shear modulus, and E the elastic modulus. From [88], we then find for each particle in the sample a linear dependency of the form:…”
Section: Explicit Particle Structures-balance Of Local Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they showed that their formalism holds for the inclusion of net torques on the rigid particles. The specified examples for twoand three-particle systems in [59,60] are of particular importance in providing a solid theoretical basis for the systems described in this work.…”
Section: Elastic Interaction Mediated By the Matrixmentioning
confidence: 99%